O tempo do cuidado entre a vida e o trabalho: contribuições para o debate jurídico do cuidado no Brasil - Cristiane dos Santos Silveira (2021)
Worldwide data shows that women spend 12.5 billion hours a day in unpaid care work (COFFEY, 2020), 76.2% of the total sum of hours spent in these activities by people of either gender. This which corresponds to 201 working days per year, considering an 8-hour workday, against 63 days worth of work for males in the same activities. of annual male work in the same activities (ILO, 2018). These numbers reveal one of the reasons why the importance of a temporal analysis of care is integral affirmed for the perception of inequalities of gender, class, race, among others that permeate this socially invisible work. Recognizing the importance of this debate, this research had two main objectives: the first was to carry out a survey of the main issues discussed in academic care literature around time. From this effort, which two main approaches were found: the relevance of perception of time in its quantitative dimension for the visualization of inequalities of gender, class, race, among others, that permeate care, and the contribution of the perception of qualitative time to the understanding of the subjective dimensions of the concrete experience of caring, the contradictory and ambivalent affects that are mobilized, the acquired skills, such as the ability to recognize the needs of others and manage everyday family life. In this way, Care is thus approached both as an exploited work, which sustains the capitalist economy but which is excluded from left out of it, being poorly or unpaid and socially undervalued, but and also as an experience that brings out what is most essential and basic in human life. Thus, In this sense, the time of care is placed between work and life, in this constant displacement carried out predominantly by women between the sphere of work and the family sphere, which generates an overlapping of activities that has negative impacts on female working and personal life. The second objective of the research was to reflect on how Labor Law deals with the time of care, which leads to the conclusion that the legal field, upon receiving the problems and disputes around this resource, which is so scarce in capitalist societies, confirms its invisibility and subordination in at least three situations: i) when establishing working hours that do not include the times of care and do not offer possibilities for paid leaves that cover the different situations in which workers and workers need to take responsibility for family care; ii) by not providing for the recognition of full-time family care as socially protected work;, and iii) by not recognizing the equal legal treatment of paid care work (domestic work) compared to other types of work. Thus, It becomes is clear that care takes place in hidden, unpaid or subordinate times, and that the Labor Law has its role in continuing this the invisibility of these times by not offering broader and more consistent social protectionsfor the different situations in which female and male workers need to move between work and life to assume care responsibilities.